Molecular approach to phase transitions in a calamitic ester substituted aroylhydrazone liquid crystal. (20th April 2016) - Nandi, Rajib; Singh, Sachin Kumar; Singh, Hemant Kumar; Shankar Rao, D. S.; Krishna Prasad, S.; Singh, Bachcha; Singh, Ranjan K.
Abstract : Temperature dependent Raman and X‐ray diffraction studies of a calamitic ester substituted aryolhydrazone liquid crystal (LC) system; N ‐[4‐(4ʹ‐decyloxy)benzoyloxy benzylidene]‐ N ʹ‐[4ʹ‐decyloxybenzoyl]hydrazine (DB2H) have been performed to investigate the molecular arrangement and intermolecular interaction environment in LC phase. X‐ray diffraction study with the help of density functional theoretical study gives the information of molecular tilt angle in SmC layer. Prominent Raman signatures of crystal I → crystal II, crystal II → SmC and SmC → Isotropic phase transitions were identified in terms of changes in peak position and linewidth as well as Raman intensity. Analysis of Raman marker bands gives evidence of residual intermolecular hydrogen bonds between amide groups responsible for tilting arrangement in SmC phase. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A temperature‐dependent Raman spectroscopic study in conjunction with XRD and DFT calculations of an ester‐substituted aryolhydrazone liquid crystal has been done to explore structural modification and molecular arrangement during phase transitions. The hydrogen bonds between the amide groups are weakened at crystal I → crystal II phase transition and reduce considerably with small residue at crystal II → SmC phase transition. The presence of hydrogen bonding between amide groups is responsible for tilting arrangement in SmC phase.